Critical Cultural Awareness and Identity Development: Insights from a Short-Term Thai Language Immersion - Chan, Wai Meng; Klayklueng, Sasiwimol (Electronic journal of foreign language teaching, 2018)
Promoting and cultivating intercultural competence is an important goal of foreign language education today. In-country language immersion, an out-of-class component of the foreign language curriculum, has the potential to contribute in this respect, as it gives learners first-hand experience in the target language country and allows them to discover and partake in the local community’s sociocultural practices. This article focuses on a study of the impact of a short-term in-country language immersion in Chiangrai, Thailand, on the development of critical cultural awareness and identity in Singapore university students of Thai as a foreign language. The study adopted a case study approach and collected qualitative data on two subjects through journals, interviews, activity observation and document inspection. The data were analysed based on Byram’s (1997, 2008) model of intercultural competence, Lave and Wenger’s (1991) Situated Learning Theory and their notion of legitimate peripheral participation, and Weinreich’s (2003) Identity Structure Analysis. The findings suggest that the immersion programme in Chiangrai provided the learners with access to legitimate peripheral participation, which helped them gain insights into the target language culture, negotiate and (co-)construct new cultural meanings and knowledge, and critically appraise both the target language and the native cultures. These experiences and a growing identification with the Thai culture prompted them to re-examine and question their own culture and identity, but led eventually to the re-affirmation and re-construction of their own identity, as they sought to extend their value systems by adopting and aspiring towards Thai traits and practices that they found desirable.